2014
DOI: 10.1590/s0004-28032014000300003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Infection With Caga-Positive Helicobacter Pylori Strains Among Children and Adolescents in Southern Brazil

Abstract: -Context -Helicobacter pylori (H. pylori) has a worldwide distribution, but the prevalence of infection, virulence factors, and clinical presentation vary widely according to the studied population. In Brazil, a continental country composed of several ethnicities and cultural habits, the behavior of infection also appears to vary, as many other studies have shown. Objective -Describe the prevalence of infection with cagA-positive H. pylori strains in a group of children and adolescents who underwent esophagoga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
8
2
Order By: Relevance
“…Regarding the distribution of genders by age group, the result found reinforces data already existing in the current literature, which does not observe significant statistical difference between genders (11,14,15) .…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the distribution of genders by age group, the result found reinforces data already existing in the current literature, which does not observe significant statistical difference between genders (11,14,15) .…”
Section: Discussionsupporting
confidence: 88%
“…This was supported by studies done by Abdel Razak, Ozbey et al, Oliveira et al who also observed pain abdomen as a common symptom in 67.5%, 57.4%, 34.6% cases, respectively. (2,7,8) Gastrointestinal bleeding was observed in studies by Oliveira et al (13.4%), Ozbey et al (11.9%), Motamed et al (9.8%), K Thakkar (5.8%) whereas we did not see any child with complaints of gastrointestinal bleed. (2,8,9,10) Under nutrition and growth retardation was observed in dyspeptic children by Ozbey et al (21.8%) and K Thakkar (2.4%).…”
Section: Discussioncontrasting
confidence: 51%
“…Chi-square value = 168.941 with a p <0.0001. (1,2) Lymphocytic infiltration was mild-to-moderate in 28 (74%) and high in 10 cases (26%) ( Figure 6). Neutrophilic infiltration was noted in four cases (10%), mildto-moderate in three cases (8%) and high in one case (3%).…”
Section: Gross Endoscopic Findingsmentioning
confidence: 96%
See 1 more Smart Citation
“…The prevalence of cagA ‐positive H. pylori was 29.6%. There were no statistically significant differences in clinical or demographic characteristics or in the endoscopic and histologic features of the patients infected with cagA ‐positive strains as compared with those infected with cagA ‐negative strains .…”
Section: Pathophysiologymentioning
confidence: 82%